PENINGKATAN KUALITAS JERAMI PADI MELALUI PENERAPAN TEKNOLOGI AMONIASI UREA SEBAGAI PAKAN SAPI BERKUALITAS DI DESA BEBALANG KABUPATEN BANGLI - Trisnadewi A. A. A. S.; N. L. G. Sumardani; B. R. Tanama Putri; I G. L. O. Cakra; I G. A. I. Aryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2011)
The community service was conducted in Bebalang village, Bangli regency and aimed to improve the knowledge and innovation technology of farmers, about the using of rice straw as a feed and how to improve its quality. The quality of rice straw including nitrogen total and digestibility could be increased by ammoniated technology using urea. The use of urea was 4% for 100 kg of rice straw or 4 kg for 100 kg of rice straw. The activity was done on Monday, October 30, 2010 and attended by 24 farmers or 100% members of subak at Sedit area, Bangli. The methods used were direct instruction and practice to the farmers. The results of the activity showed that the farmers’ knowledge was improved and the farmers want to apply the ammoniated rice straw as alternative feed for ruminant.